2019
DOI: 10.1021/acschemneuro.9b00289
|View full text |Cite
|
Sign up to set email alerts
|

Oleic Acid Coated Silver Nanoparticles Showed Better in Vitro Amoebicidal Effects against Naegleria fowleri than Amphotericin B

Abstract: Naegleria fowleri (N. fowleri) causes primary amoebic meningoencephalitis (PAM) which almost always results in death. N. fowleri is also known as “brain-eating amoeba” due to its literal infestation of the brain leading to an inflammatory response in the brain tissues. Currently, there is no single drug that is available to treat PAM, and most treatments are combinations of antifungal, anticancer, and anti-inflammatory drugs. Recently nanotechnology has gained attention in chemotherapeutic research converging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…The synthesized nano carrier was screened for its cytotoxicity using MTT assay. Human cervical adenocarcinoma cells (HeLa) (ATCC ® CCL-2™), were obtained from American Type Culture Collection (ATCC),and cultured in Roswell Park Memorial Institute (RPMI) 1640 medium, supplemented with 10% foetal bovine serum, 1% minimum essential medium amino acids, 1% l -glutamine and 1% antibiotics at 37 °C with 5% CO 2 (Rajendran et al 2019 ). NIH 3T3 cells (ATCC CRL-1658) were purchased from the ATCC and cultured in Dulbecco`s modified eagle`s medium (DMEM) having foetal bovine serum (10%) (Invitrogen, USA) and antibiotics (streptomycin and penicillin—about 50 U/mL).Both cell lines were incubated into well plates with 96 wells and 8 × 10 3 and 6 × 10 4 cells/well thickness, individually, in a (200 µL) refined media.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesized nano carrier was screened for its cytotoxicity using MTT assay. Human cervical adenocarcinoma cells (HeLa) (ATCC ® CCL-2™), were obtained from American Type Culture Collection (ATCC),and cultured in Roswell Park Memorial Institute (RPMI) 1640 medium, supplemented with 10% foetal bovine serum, 1% minimum essential medium amino acids, 1% l -glutamine and 1% antibiotics at 37 °C with 5% CO 2 (Rajendran et al 2019 ). NIH 3T3 cells (ATCC CRL-1658) were purchased from the ATCC and cultured in Dulbecco`s modified eagle`s medium (DMEM) having foetal bovine serum (10%) (Invitrogen, USA) and antibiotics (streptomycin and penicillin—about 50 U/mL).Both cell lines were incubated into well plates with 96 wells and 8 × 10 3 and 6 × 10 4 cells/well thickness, individually, in a (200 µL) refined media.…”
Section: Methodsmentioning
confidence: 99%
“…Amoebicidal assays were performed as previously described (Rajendran et al 2019 ). Briefly, 5 × 10 5 amoebae were incubated with compounds at various concentrations for 24 h at 30 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In more recent years, nanoparticles have gained attention in the pharmaceutical industry for their ability to enhance the efficacy of a drug, which allows a decrease in dosage [ 63 ]. Since nanoparticle drug delivery systems have been demonstrated to increase bioavailability, decrease cell toxicity, and are site-specific, there have been a few studies determined to understand the advantages of using drugs conjugated with nanoparticles to treat PAM ( Table 3 ) [ 80 ].…”
Section: Potential Treatmentmentioning
confidence: 99%
“…The study concluded that 10 µM of OA-AgNp was able to reduce the number of N. fowleri from 6.1 × 10 5 to 2.1 × 10 5 . This conjugation exhibited higher activity against the trophozoites than AmB, which reduced the amoeba to 2.7 × 10 5 [ 80 ]. Another study investigated the conjugation of three different FDA-approved drugs to reduce the number of N. fowleri trophozoites.…”
Section: Potential Treatmentmentioning
confidence: 99%
“…More recently, a follow-up study from the same group looked at the effect of oleic acid-coated silver nanoparticles (OA-AgNPs) with a mean diameter comprised between 45 and 90 nm against N. fowleri [119]. OA is a naturally occuring monounsaturated omega-9 fatty acid, which has been associated with health benefits, such as hypotensive or anti-inflammatory effects; it also exhibited potent antiacanthamoebic activity against Acanthamoeba castellanii [120,121].…”
Section: Rare Brain Infectious Diseases-how Nanomedicine Can Repurpose Clinically Approved Drugsmentioning
confidence: 99%